2022
DOI: 10.1039/d2fo01981g
|View full text |Cite
|
Sign up to set email alerts
|

An α type gluco-oligosaccharide from brown algae Laminaria japonica stimulated the growth of lactic acid bacteria encoding specific ABC transport system components

Abstract: We determined a novel neutral α type gluco-oligosaccharide from the brown alga Laminaria japonica with a degree of polymerization (DP) of 2-8 and a structure that mainly consists of α-(1→4)-linked...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, there are only a few studies showing the utilization of oligosaccharides derived from marine biomass by LAB. In this area Jin et al [34] showed that a variety of lactic acid bacteria species including Lactobacillus plantarum encode specific transporter system for utilization of α-gluco-oligosaccharides derived from brown seaweed Laminaria japonicus. However, there is a lack of evidence regarding the growth of LAB on β-gluco-oligosaccharides derived from seaweed.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are only a few studies showing the utilization of oligosaccharides derived from marine biomass by LAB. In this area Jin et al [34] showed that a variety of lactic acid bacteria species including Lactobacillus plantarum encode specific transporter system for utilization of α-gluco-oligosaccharides derived from brown seaweed Laminaria japonicus. However, there is a lack of evidence regarding the growth of LAB on β-gluco-oligosaccharides derived from seaweed.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies show the utilization of oligosaccharides derived from marine biomass by LAB. In this area, Jin et al [36] showed that various lactic acid bacteria species, including L. plantarum, encode specific transporter systems for the utilization of α-gluco-oligosaccharides derived from the brown seaweed Laminaria japonicus. However, there is a lack of evidence regarding the growth of LAB on β-gluco-oligosaccharides derived from seaweed.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, ATP is hydrolysed by NBD and TMD returns to its original state to initiate a new transportation cycle [ 83 ]. This transport system has been associated with the uptake by the probiotic species of several prebiotics such as inulin (a fructose polymer), galactooligosacharide (GOS), raffinose (glucose + fructose + galactose), panose (a glucose trimer), xylobiose (a xylose dimer) and xylooligossacharide (XOS) and other sugars [ 82 , 84 , 85 , 86 ]. The lack of this transport can influence in the production process that use substrates enriched in some of these sugars, as well as reduce the fitness of probiotic during colonization of GIT, mainly in neonates that have a diet composed of their mother’s milk with several oligosaccharides [ 87 ].…”
Section: From the Physiology Of Production To The Processing Of The P...mentioning
confidence: 99%